2007
DOI: 10.4322/rbcv.2014.229
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência de anticorpos homólogos anti-Borrelia burgdorferi em eqüinos de propriedades dos municípios de Três Rios e Vassouras, estado do Rio de Janeiro

Abstract: ResumoBorrelia burgdorferi é uma espiroqueta transmitida por carrapatos, de ampla distribuição geográfica, que acomete o homem e animais domésticos, tendo os animais silvestres como reservatórios. O presente estudo teve como objetivo relatar a ocorrência de eqüinos soropositivos para B. burgdorferi, por meio de inquérito soroepidemiológico utilizando o ensaio de imunoadsorção enzimática (ELISA) indireto. Procedeu-se a análise sorológica de 747 soros de eqüinos, onde 431 pertenciam ao município de Três Rios e 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In Brazil, seroepidemiological studies on domestic animals have already detected antibodies against B. burgdorferi in dogs (SOARES et al, 1999), horses (MADUREIRA et al, 2007;GALLO et al, 2009) and cattle (GUEDES JUNIOR et al, 2008). The frequency of seropositive buffaloes in the present work (83.9%) was markedly greater than the rate of 54.9% observed among cattle (GUEDES JUNIOR et al, 2008) and the 26.7% found among horses (GALO et al, 2009), in the same region.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, seroepidemiological studies on domestic animals have already detected antibodies against B. burgdorferi in dogs (SOARES et al, 1999), horses (MADUREIRA et al, 2007;GALLO et al, 2009) and cattle (GUEDES JUNIOR et al, 2008). The frequency of seropositive buffaloes in the present work (83.9%) was markedly greater than the rate of 54.9% observed among cattle (GUEDES JUNIOR et al, 2008) and the 26.7% found among horses (GALO et al, 2009), in the same region.…”
Section: Discussionmentioning
confidence: 99%
“…Madureira and co-workers 47 observed a frequency of 28.4% of anti- Borrelia homologous ELISA antibodies in horses in the municipalities of Três Rios and Vassouras, Rio de Janeiro State, whereas the frequency was 26.7% in the municipality of Belém, Pará State 48 . Guedes Junior and co-workers 49 identified 54.9% of cattle as being seropositive in the state of Paraná.…”
Section: Borreliosis In Horsesmentioning
confidence: 98%
“…antibodies. Madureira et al (2007) reported that 28.4% of horses showed seropositivity in Minas Gerais State, and Galo et al (2009) diagnosed the disease in 26.7% of horses in Pará State. In Campo Grande, Mato Grosso do Sul State, it was verified seropositivity for B. burgdorferi in 20.6% in the sampled horses (n=262) (Campos et al, 2021).…”
Section: Introductionmentioning
confidence: 99%